2012
DOI: 10.1097/jsm.0b013e31823a46ce
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2-Dimensional Measurement Techniques for Predicting Knee Angle and Moment During a Drop Vertical Jump

Abstract: Objective To determine the association of two dimensional (2D) video-based techniques and three-dimensional (3D) motion analysis to assess potential knee injury risk factors during jump landing. Design Observational study Setting Research Laboratory Participants Thirty-six female athletes in cutting and pivoting sports. Assessment Athletes performed a drop vertical jump during which movement was recorded with a motion analysis system and a digital video camera positioned in the frontal plane. Main Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 28 publications
0
49
3
Order By: Relevance
“…Interestingly, this value corresponded closely to the valgus angles for participants displaying poor control in the current study. Another study 24 compared the frontal plane projection angle and knee separation distance measured from 2-D video recordings and 3-D motion analysis and reported intraclass correlation coefficients of 0.89 to 0.97, demonstrating higher agreement than that reported in the current study. This is logical, as video analysis permits a more standardized and detailed assessment than real-time observational screening.…”
Section: Discussion Tcontrasting
confidence: 51%
See 4 more Smart Citations
“…Interestingly, this value corresponded closely to the valgus angles for participants displaying poor control in the current study. Another study 24 compared the frontal plane projection angle and knee separation distance measured from 2-D video recordings and 3-D motion analysis and reported intraclass correlation coefficients of 0.89 to 0.97, demonstrating higher agreement than that reported in the current study. This is logical, as video analysis permits a more standardized and detailed assessment than real-time observational screening.…”
Section: Discussion Tcontrasting
confidence: 51%
“…Higher agreement has been found for vertical drop-jump assessments, with agreement of 88% to 93% and corresponding kappa coefficients of 0.75 to 0.85 in 1 study 10 and intraclass correlation coefficients of 0.89 and 0.92 in another. 24 However, the drop-jump assessments in these studies were based on video reviews, and only 1 study 31 has investigated real-time assessment of knee kinematics during a vertical drop-jump task. Stensrud et al 31 reported good agreement between realtime visual evaluation of knee control during a vertical drop-jump landing task and 2-D video analysis of knee valgus.…”
Section: T T Resultsmentioning
confidence: 99%
See 3 more Smart Citations